A luminescent sensor based on a Zn(ii) coordination polymer for selective and sensitive detection of NACs and Fe3+ ions. Issue 12 (1st March 2019) - Zhang, Xiao; Zhuang, Xinrui; Zhang, Nanxi; Ge, Chunyu; Luo, Xuan; Li, Jinxue; Wu, Jie; Yang, Qingfeng; Liu, Rui
Abstract : To design an effective fluorescence probe for sensing nitroaromatic compounds and metal ions, a novel two-dimensional coordination polymer, {Zn2 (NO3 )2 (4, 4′-bpy)2 (TBA)}, was synthesized via a hydrothermal method. Abstract : To design an effective fluorescence probe for sensing nitroaromatic compounds (NACs) and metal ions, a novel two-dimensional (2D) coordination polymer, {Zn2 (NO3 )2 (4, 4′-bpy)2 (TBA)} (1 ) {H2 TBA = 4-(1 H -tetrazol-5-yl)-benzoic acid, 4, 4′-bpy = 4, 4′-bipyridine} was synthesized via a hydrothermal method. As expected, 1 presented varying degrees of fluorescence intensity changes for detecting and recognizing trace NACs with high selectivity and sensitivity in water solution. Moreover, 1 not only exhibited a highly selective fluorescence quenching effect on Fe 3+ ions in aqueous solution, but could also resist the interference of various other metal ions. In addition, it has been found that the fluorescence quenching mechanisms among NACs and Fe 3+ ions are mainly related to the interactions between the host group and guest molecules by energy and electron transfer.